Integration of organic amendments and bioagents in suppressing cumin wilt caused by Fusarium oxysporum f. sp. cumini - S. GANGOPADHYAY*, NITIN CHAWLA1 and (Indian Phytopathology, 2009)
Antagonistic potentiality of Trichoderma harzianum, T. viride, Pseudomonas fluorescens and Bacillus subtilis against Fusarium oxysporum f. sp. cumini was tested under laboratory and greenhouse conditions. The effect of organic amendments viz., farm yard manure, vermicompost and mustard cake on disease control efficacy of four antagonists against Fusarium wilt was studied. Maximum inhibition of mycelia growth of F. oxysporum f. sp. cumini was recorded in presence of P. fluorescens closely followed by T. harzianum. Seed treatment with talc based formulations of P. fluorescens and T. harzianum provided excellent control of Fusarium wilt under green house condition. These bioagents suppressed the pathogen population in soil and also enhanced the shoot and root lengths and dry weight of cumin plants. Disease incidence as well as pathogen population in soil were significantly reduced in response to seed treatment with bioagents and simultaneous application of organic amendments. These treatments also led to considerable increase in shoot and root lengths and dry weight of cumin plants. The biocontrol potentiality of T. harzianum and P. fluorescence was relatively better in presence of farm yard manure or mustard cake. While disease control due to seed treatment with T. viride, T. harzianum or P. fluorescens was similar in presence of vermicompost.